EFFECT OF SOME AJUGA IVA LEAF EXTRACTS ON CERTAIN BIOLOGICAL ASPECTS OF THE GREATER WAX MOTH (GALLERIA MELLONELLA L.). - Al-Zubaie , Alaa; Al-khazraji, Hind (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was conducted to determine the effect of treating the food of third-instar larvae of the greater wax moth (Galleria mellonella) with ethanol and hexane extracts of Ajuga iva leaves at concentrations of 5%, 7.5%, and 10%, and their impact on the biological aspects of the insect. The results showed that the 10% concentration achieved the highest larval mortality rate, with an average of 51.84% for both extracts, while the lowest mortality rate was 19.17% at the 5% concentration, and 3.33% in the control treatment. Additionally, there was a reduction in the percentage of larvae that pupated, with the ethanol extract being more effective in reducing the number of pupae its reached average 61.68% and 82.53% for the ethanol and hexane extracts, respectively, compared to 96.70% in the control treatment. The highest rate of pupal deformities was observed when treated with the 10% ethanol extract. It was also noted that the ethanol extract significantly prolonged the larval and pupal stages. The results also indicated that the 10% ethanol extract had the highest impact in reducing the adult longevity, reduced the number of eggs and laid by females reduced the egg hatch rate.